2013
DOI: 10.3390/jpm3040275
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Social Networking and Sharing Behaviors among Consumers of Direct-to-Consumer Personal Genomics

Abstract: Little is known about how consumers of direct-to-consumer personal genetic services share personal genetic risk information. In an age of ubiquitous online networking and rapid development of social networking tools, understanding how consumers share personal genetic risk assessments is critical in the development of appropriate and effective policies. This exploratory study investigates how consumers share personal genetic information and attitudes towards social networking behaviors. Methods: Adult participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The characteristics of the 19 articles, involving 11 unique studies (see Table 1 , column 9 for details), included in the systematic review can be found in Table 1 . Six studies had a cross-sectional design (Egglestone et al 2013 ; Gordon et al 2012 ; Kaufman et al 2012 ; Lee et al 2013 ; McGrath et al 2016 ; McGuire et al 2009 ), three were longitudinal observational studies (Bloss et al 2011b , 2013 ; Boeldt et al 2015 ; Carere et al 2016 ; Darst et al 2013 , 2014 ; Kaphingst et al 2012 ; O’Neill et al 2015 ; Reid et al 2012 ; van der Wouden et al 2016 ) and two were intervention studies (Haga et al 2014 ; James et al 2011 ). The number of participants ranged from 60 to 2037, totalling 6672 unique participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the 19 articles, involving 11 unique studies (see Table 1 , column 9 for details), included in the systematic review can be found in Table 1 . Six studies had a cross-sectional design (Egglestone et al 2013 ; Gordon et al 2012 ; Kaufman et al 2012 ; Lee et al 2013 ; McGrath et al 2016 ; McGuire et al 2009 ), three were longitudinal observational studies (Bloss et al 2011b , 2013 ; Boeldt et al 2015 ; Carere et al 2016 ; Darst et al 2013 , 2014 ; Kaphingst et al 2012 ; O’Neill et al 2015 ; Reid et al 2012 ; van der Wouden et al 2016 ) and two were intervention studies (Haga et al 2014 ; James et al 2011 ). The number of participants ranged from 60 to 2037, totalling 6672 unique participants.…”
Section: Resultsmentioning
confidence: 99%
“…The number of participants ranged from 60 to 2037, totalling 6672 unique participants. Six unique study populations (Carere et al 2016 ; Egglestone et al 2013 ; Kaufman et al 2012 ; Lee et al 2013 ; McGrath et al 2016 ; McGuire et al 2009 ; van der Wouden et al 2016 ) involved actual consumers who paid the full or a reduced retail price for the product. The remaining five studies (Bloss et al 2011b , 2013 ; Boeldt et al 2015 ; Darst et al 2013 , 2014 ; Gordon et al 2012 ; Haga et al 2014 ; James et al 2011 ; Kaphingst et al 2012 ; Reid et al 2012 ) included participants who were offered genetic testing for free as part of a research trial (henceforth referred to as non-actual consumers).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical and legal dilemmas faced by researcher-driven or biobank-driven genomic data sharing have been extensively discussed in the literature (Fullerton et al 2010 ; Harris et al 2012 ; Kaye et al 2009 ; Knoppers et al 2011 ). A few studies also have reflected on attitudes of consumers concerning sharing personal genomic data (Lee et al 2013 ) and policies employed by direct-to-consumer genetic testing companies regarding their research activities fueled by consumer data (Esposito and Goodman 2009 ; Harris et al 2013 ; Howard et al 2010 ). However, little has been published about the ethical and legal challenges surrounding growing web-based personal genomic data sharing (Bloss 2013 ; Angrist 2014 ; Mathews and Jamal 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a likely shortage of knowledge and experience of general health care professionals in genetics may hinder such consultation. In this regard, a survey of consumers of Direct-to-Consumer personal genomics indicated “the majority of participants reported that their healthcare provider had limited ability to understand and insufficient expertise to interpret their results” (Lee et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%